Pi of the sky full system and the new telescope - Mankiewicz, L.; Batsch, T.; Castro-Tirado, A.; Czyrkowski, H.; Cwiek, A.; Cwiok, M.; Dabrowski, R.; Jelínek, M.; Kasprowicz, G.; Majcher, A.; Majczyna, A.; Malek, K.; et al. (Universidad Nacional Autonoma de Mexico, 2014)
The Pi of the Sky is a system of wide field of view robotic telescopes, which search for short timescale astrophysical phenomena, especially for prompt optical GRB emission. The system was designed for autonomous operation, monitoring a large fraction of the sky to a depth of 12*m - 13*m and with time resolution of the order of 1-10 seconds. The system design and observation strategy were successfully tested with a prototype detector operational at Las Campanas Observatory, Chile from 2004-2009 and moved to San Pedro de Atacama Observatory in March 2011. In October 2010 the first unit of the final Pi of the Sky detector system, with 4 CCD cameras, was successfully installed at the INTA El Arenosillo Test Centre in Spain. In July 2013 three more units (12 CCD cameras) were commissioned and installed, together with the first one, on a new platform in INTA, extending sky coverage to about 6000 square degrees.